Motivating factors influencing the career advancement of nurses into nursing management positions - S. A Mohammed; A. Al Jaffane; M. Al Qahtani (Elsevier, 2024)
Background: Nurse motivation is a prerequisite for improved patient outcomes, performance and job satisfaction. There are studies discussed the factors influencing nurses' motivation and the job performance however little research has been conducted on the factors influencing the career advancement of nurses to nursing management positions which can bridge the gap in this area. Objectives: The aim of the study was to comprehend the intrinsic, extrinsic, and demographic motivation factors that influence nurses' career advancement into nursing management positions. Methods: This study employed a quantitative, cross sectional and descriptive design. A self-administered questionnaire was distributed among 158 nurses who were either planning to advance their career in nursing management in the future (131) or working in Saudi Arabian hospitals in nursing management positions (27) at the time of study. A preliminary study was also conducted prior to the main study. A self-administered questionnaire, measured using a 7-point Likert scale was used for the study. The study utilized SPSS-19 software pack and descriptive analysis for analyzing data. Results: The results of the study indicated that the intrinsic motivation factors that influenced the nurses to advance the career into nursing management positions included joy and happiness (p = 0.002), sense of personal accomplishment (p = 0.025), independence in the job (p = 0.010), achievements in life (p = 0.000), freedom of doing the job effectively (p = 0.027), reassurance (p = 0.000), personal satisfaction (p = 0.007), self-esteem (p = 0.012), job discrimination at base-level positions (p = 0.001), responsibility (p = 0.000), and opportunities to use their abilities (p = 0.007). The extrinsic motivation factors that motivated the nurses included the provision of more educational opportunities (p = 0.006), more flexibility in family life (p = 0.001), more suitable for a healthy living (p = 0.022), and opening up more career prospects (p = 0.046), among others. Finally, the demographic factors that motivated nurses included sex (p = 0.001), marital status (p = 0.000), current nursing job (p = 0.025), and total years of nursing experience (p = 0.018). Conclusions: The present study demonstrated that intrinsic, extrinsic and demographic factors motivated nurses to advance their careers into nursing management positions in the Kingdom of Saudi Arabia. Accordingly, the study renders important implications for the career development of nurses in relation to nursing management roles.